EX-SITU Characterization of Luffa aegyptaica in Lagos State, Nigeria (Baghdad Science Journal, 2020)
Luffa aegyptiaca is a plant of multi-purpose importance whose usefulness cuts across virtually all areas of life. This study has characterized L. aegyptiaca in Lagos state and determined the mineral, proximate, phytochemical as well as the heavy metal accumulation potential. Samples were collected from the 20 Local Government Areas (LGAs) in Lagos state at 2 samples per location. Genetic similarity and intra-specific variation in 40 samples of L. aegyptiaca were determined using 3 Random Amplified Polymorphic DNA (RAPD) primers which yielded a total of 42 markers of which 25 was polymorphic. The maximum number of bands (14) was produced by OPC4 while the minimum (7) were produced by OPAF20. Percentage polymorphisms were 70% (OPAF20), 82.4% (OPC4) and 68.4% (OPC6) with an average value of 73.6%. The result from a genetic diversity study was scored to generate a dendrogram using NTsys (2.0j). Phytochemical, proximate, Mineral and the heavy metal study showed the presence of Flavonoid, Saponin; Carbohydrate, protein; Sodium (Na), Calcium (Ca) and Chromium, Iron, Copper, Zinc, Lead among others. The nutritional composition and the potentials of the RAPD marker in distinguishing intra-specific variation in Luffa aegyptiaca were highlighted in this study.